Pulmonary alveolar proteinosis: A case report and literature review - yasaman Sajadi; Simin Moudi; Ehsan Chogan; Mahmood Monadi (Caspian Journal of Internal Medicine)
Background: Pulmonary alveolar proteinosis (PAP) is a rare disease caused by the accumulation of surfactant in the lung's alveoli, as a result of malfunction in the cleaning function of alveolar macrophages. The major symptoms include cough and dyspnea. Computed tomography scan usually reveals crazy-paving pattern. Lung biopsy confirms the diagnosis by showing accumulations of periodic acid-schiff-positive lipoproteinaceous materials. Case Presentation: In this report, we present a middle-age man with progressive dyspnea on exertion, and frequent cough with no noteworthy medical history. The results of initial examinations and laboratory tests were non-diagnostic, so imaging studies were requested for the patient. After imaging and suspecting PAP as a differential diagnosis due to results of high resolution computed tomography, a transbronchial biopsy was performed to confirm the diagnosis. Then, according to the histopathology reports, the diagnosis of PAP was made. During the biopsy procedure, the patient developed pneumothorax, and accurate treatment approaches were considered for this complication. Conclusions: In patients with chronic progressive dyspnea and cough, appropriate and timely imaging and other paraclinic investigations must be considered by the physicians.